2021
DOI: 10.1016/j.heliyon.2021.e06851
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of Rhodamine B dye from aqueous solution by using graphene–based nickel nanocomposite

Abstract: In this work, reduced graphene oxide-nickel (RGO–Ni) nanocomposite is synthesized. X-ray diffraction (XRD), scanning electron microscopy (SEM) and SEM–EDS (Energy Dispersive X-Ray Spectroscopy) are used to study the crystalline nature, morphology and elemental composition of the RGO–Ni nanocomposite, respectively. As synthesized RGO–Ni nanocomposite is used to develop selective adsorptive removal of Rhodamine B (RhB) dye from the aqueous solution. The experiments have been performed to investigate RhB uptake v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…It is shown that about 96.84% methylene blue adsorbed within 60 min and 98% crystal violet adsorbed within 100 min and also that rate of adsorption decreases with increasing time for both dyes. Higher rate of adsorption at initial stage is due to maximum number of vacant pores on the adsorbent and high gradient of dye concentration [60]. The difference in the rate of adsorption may be due to fact that initially due to remaining vacant sites of the adsorbent, the adsorbates are getting attached very quickly.…”
Section: Adsorption Studymentioning
confidence: 99%
“…It is shown that about 96.84% methylene blue adsorbed within 60 min and 98% crystal violet adsorbed within 100 min and also that rate of adsorption decreases with increasing time for both dyes. Higher rate of adsorption at initial stage is due to maximum number of vacant pores on the adsorbent and high gradient of dye concentration [60]. The difference in the rate of adsorption may be due to fact that initially due to remaining vacant sites of the adsorbent, the adsorbates are getting attached very quickly.…”
Section: Adsorption Studymentioning
confidence: 99%
“…Carbon-based nanocomposites have a better regeneration ability. In studies on the adsorption removal of rhodamine B dye using GO-based nano-nickel composite materials, the adsorption efficiency decreased from 90% to 85% after the first recovery and decreased to 60% after the fifth recovery [ 125 ].…”
Section: Application In Wastewatermentioning
confidence: 99%
“…Adsorption has been widely used over the years because of its rather high efficiency, easy operation, relatively inexpensive, and reversibility and desorption capability [ 13 , 14 ]. Aside from the elimination of heavy metals, adsorption is regularly used for dye removal [ 14 , 15 ]. However, the cost of the adsorption process is mainly related to the adsorbent.…”
Section: Introductionmentioning
confidence: 99%